Towards Islamic ethics in professional penetration testing - Habaebi, Mohamed Hadi (Revelation and Science, IIUM, 2013)
Frequent technological advances in the field of computing have resulted in a rapid increase in creation of new loopholes in systems. To secure their computing systems, big companies resort to use penetration testing as a solution whereby an external company is hired to evaluate the security of the computer system or network under perspective. There are many Muslim professionals who have an effective role in many stages of the penetration testing process and have access to vital technical information about many companies. Failing to secure the critical information or a misuse may result in acute data leak. Reason demands that these professionals understand the ethics involved and implement them skillfully and understand that ethics holds a high place in Islam. This paper highlights the key ethical steps and presents issues arising in a modern penetration testing background. Then, it relates traditional ethical principles to a solution attempting to resolve the problems using the framework of Islamic ethical values; which are derived from the Holy Qur’an and Sunnah and provide a high standard of ethics on all levels for Muslims. Keywords: Network Security, Penetration Testing, Social Ethics